Comparative study of ethanol sensor based on gold nanoparticles: ZnO nanostructure and gold: ZnO nanostructure - E. Wongrat (2018)
Gold colloid:ZnO nanostructures were prepared from Zn powder by using thermal oxidation technique on alumina substrates, then it was impregnated by gold colloid for comparative study. The gold colloid is the solution prepared by chemical reduction technique; it appeared red color for gold nanoparticle solution and yellow color for gold solution. The heating temperature and sintering time of thermal oxidation were 700 °C and 24 h, respectively under oxygen atmosphere. The structural characteristics of gold colloid:ZnO nanostructures and pure ZnO nanostructures were studied using filed emission scanning electron microscope (FE-SEM). From FE-SEM images, the diameter and length of gold colloid:ZnO nanostructures and ZnO nanostructures were in the ranges of 100-500 nm and 2.0-7.0 μm, respectively. The ethanol sensing characteristics of gold colloid:ZnO nanostructures and ZnO nanostructures were observed from the resistance alteration under ethanol vapor atmosphere at concentrations of 50, 100, 200, 500, and 1000 ppm with the operating temperature of 260-360 °C. It was found that the sensitivity of sensor depends on the operating temperature and ethanol vapor concentrations. The sensitivity of gold colloid:ZnO nanostructures were improved with comparative pure ZnO nanostructures, while the optimum operating temperature was 300 °C. The mechanism analysis of sensor revealed that the oxygen species on the surface was O 2-. Crown Copyright © 2009.